(untitled) (Social Science Review, 2023)
The outbreak of COVID-19 imposed an adverse effect on mental health across the globe, and when it comes to children with special needs facing a rapid change in their daily routine, an unfulfillment of their higher healthcare needs and inability to communicate appropriately may increase the risk. This study aims to examine the effect of COVID-19 on mental health in children with Communication Disorders in Bangladesh. Data were collected over the phone among 210 parents from urban and rural areas having a child with Communication Disorders. The child’s general socio- demographic information and clinical characteristics were reported through a bivariate test, while the risk factors associated with developing anxiety were measured using Generalized Anxiety Disorder (GAD-6) scales. The result shows that children aged 11-15 suffer from severe anxiety (28.6%), and children who do not possess any language level 20(9.5%) have severe anxiety. Similarly, among children from families with Covid-19 positivity, 42(20.0%) of them have a severe level of anxiety. Therefore, counseling services should be provided to the families of COVID-19 positivity. Besides, speech and language therapy services must be ensured, as children without a language level are more prone to anxiety. Social Science Review, Vol. 39(1), June 2022 Page 1-14